Effects of rowing stroke rates on lower extremity intra-joint coordination variability in experienced young rowers - Pakravan, Faezeh; Abbasi, Ali; Noorinezhad, Zahra; Svoboda, Zdenek; Tazji, Mehdi Khaleghi; Dastmanesh, Siavash (PloS one, 2023)
The purpose of this study was to examine the effects of rowing stroke rates on lower extremity intra-joint coordination variability in professional rowers. Fifteen experienced young rowers volunteered to participate in this study. Kinematic data were recorded at different rowing speeds with seven Vicon cameras. The continuous relative phase (CRP) and CRP variability (CRPV) were used to calculate joint coordination and coordination variability, respectively, for the hip, knee, and ankle in the sagittal and horizontal planes, and a comparison was made among different rowing stroke rates. A vector analysis repeated measure ANOVA using statistical parametric mapping revealed that there were statistically significant differences in the hip-ankle, hip-knee, and knee-ankle CRPs for rowing at different stroke rates. Moreover, there was higher CRPV in the mid-drive and mid-recovery phases and less variability in the transition from the drive phase to the recovery phase. The results demonstrate the importance of knee joint in rowing tasks in experienced rowers during submaximal rowing stroke rate and the shift of movement to the hip at higher rowing stroke rate. Moreover, there was a smaller variability during drive-to-recovery transition, which may suggests an increased risk for overuse injuries.
Keywords: koleno; Water Sports; Knee; biomechanika; lidé; kotník; Sports; dolní končetina; Lower Extremity; vodní sporty; sporty; Biomechanical Phenomena; Ankle; Humans